2015
DOI: 10.18632/oncotarget.5420
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and late toxicities of 869 patients with nasopharyngeal carcinoma treated with definitive intensity modulated radiation therapy: new insight into the value of total dose of cisplatin and radiation boost

Abstract: This study was to report the long-term outcomes and toxicities of nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiation therapy (IMRT). From 2009 to 2010, 869 non-metastatic NPC patients treated with IMRT were retrospectively enrolled. With a median follow-up of 54.3 months, the 5-year estimated local recurrence-free survival (LRFS), regional recurrence-free survival (RRFS), distant metastasis-free survival (DMFS), disease-free survival (DFS) and overall survival (OS) were 89.7%, 94.5%, 85.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 44 publications
10
71
2
Order By: Relevance
“…However we compared with the prognosis of 869 NPC patients with IMRT during the same period in our hospital [25]. The 5-year OS, LRFS, and DMFS rates were 84.0%, 89.7%, and 85.6%, which were similar to our study.…”
Section: Discussionsupporting
confidence: 83%
“…However we compared with the prognosis of 869 NPC patients with IMRT during the same period in our hospital [25]. The 5-year OS, LRFS, and DMFS rates were 84.0%, 89.7%, and 85.6%, which were similar to our study.…”
Section: Discussionsupporting
confidence: 83%
“…But the courses were always interrupted or postponed in many patients as a result of adverse effects, especially for mucosal toxicity [20]. Similarly, our meta-analysis showed that patients in weekly cisplatin group had significant difficulty in achieving targeted dose of 200 mg/m 2 (RR=0.82, p=0.009) (Supplementary Figure S6), eventually, resulting in a worse survival benefit due to more treatment delay/interrupt and inadequate dose of cisplatin [2122]. There is an urgent need that a longer follow-up work and higher quality of clinical trials were performed to test the ideas.…”
Section: Discussionmentioning
confidence: 92%
“…In 370 consecutive cases of locally advanced NPC treated with IMRT with or without concurrent chemotherapy, Lin et al demonstrated that patients who received TPF induction chemotherapy achieved an OS rate of 89% at 3 years. Similarly, Ou et al reported that the 5‐year OS rate was 80.7% for a subgroup of locally advanced NPC patients who received induction chemotherapy (mostly with TP/TPF but a few with gemcitabine‐based chemotherapy) followed by IMRT versus 71.4% for those who did not ( P = .057). The numbers of induction chemotherapy cycles used in these 2 retrospective studies were not standardized, but most patients received 2 or 3 cycles.…”
Section: Discussionmentioning
confidence: 96%